TINJAUAN YURIDIS MENGENAI PEMBATASAN TANGGUNG JAWAB PELAKU USAHA MINUMAN DALAM KEMASAN TERHADAP UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - HARRY CHRISTIAN LUMBAN TOBING (JURNAL CIVIL LAW USU, 2013)
Abstract : The use of drinking water through source water in the soil is increasingly unlikely because of the depleting ground water supply and pollution. For that improved business prospects of drinking water in containers (AMDK) which include drinking water product so that it becomes an alternative for the community in meeting the needs of clean water that is safe to be consumed per day. Problems often faced by consumers with regard to any AMDK regarding health standards do not comply with the provisions of which have been set out in the decision of the Minister of health No. 907/Menkes/SK/VII/2002 about terms and monitoring the quality of drinking water.   Kata Kunci : Pelaku Usaha AMDK, UU No.8/1999, Perlindungan Konsumen.